2012
DOI: 10.1002/jeab.3
|View full text |Cite
|
Sign up to set email alerts
|

Social Discounting and the Prisoner's Dilemma Game

Abstract: Altruistic behavior has been defined in economic terms as “…costly acts that confer economic benefits on other individuals” (Fehr & Fischbacher, 2003). In a prisoner’s dilemma game, cooperation benefits the group but is costly to the individual (relative to defection), yet a significant number of players choose to cooperate. We propose that people do value rewards to others, albeit at a discounted rate (social discounting), in a manner similar to discounting of delayed rewards (delay discounting). Two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
0
28
0
6
Order By: Relevance
“…Indeed, closeness among friends has been linked to the amount of money individuals are willing to give up for another person, and to decisions to cooperate in a prisoner's dilemma (Jones & Rachlin, 2006;Locey, Safin, & Rachlin, 2013). To test whether dynamically engaged smiling was an independent signal of cooperative intent, we include a measure of self-reported liking as a covariate in our model.…”
Section: The Current Studymentioning
confidence: 99%
“…Indeed, closeness among friends has been linked to the amount of money individuals are willing to give up for another person, and to decisions to cooperate in a prisoner's dilemma (Jones & Rachlin, 2006;Locey, Safin, & Rachlin, 2013). To test whether dynamically engaged smiling was an independent signal of cooperative intent, we include a measure of self-reported liking as a covariate in our model.…”
Section: The Current Studymentioning
confidence: 99%
“…In prior experiments, Stony Brook students, playing a one-shot 1-2-9-10 PD game (B in Figure 1) with hypothetical rewards and anonymous OP, indeed cooperated at a higher rate than did those playing the 1-2-3-4 PD game (A in Figure 1) (Locey, Safin, & Rachlin, 2013); a corresponding result was found for Stony Brook students playing a face-to-face IPD game with real rewards (Safin et al, 2013). However, Safin et al (2013) found a significant correlation in cooperation rates between partners in the IPD game, which suggests that reciprocation may have played a role in fostering cooperation or defection.…”
mentioning
confidence: 89%
“…sets, the SDT in some experiments has been employed in tandem with other experimental tasks, including Probability (PDT) and Delay Discounting Tasks (DDT) (in Economics better known as risk and time preference elicitation) (Boyer et al, 2012;Rachlin & Jones, 2008b;Yi et al, 2012;Ziegler & Tunney, 2012) as well as the Prisoner's Dilemma (PD) (Locey, Safin & Rachlin, 2013) and Public Goods Game (PGG) (Jones & Rachlin, 2009 implemented the SDT in a neuro-economics experiment, while Kaplan, Reed and McKerchar (2014) investigate the link of social discounting with experimental choices on environmental loss.…”
Section: Settingsmentioning
confidence: 99%